Computer network operations and ‘rule-with-law’ in Australia - Adam Molnar; Christopher Parsons; Erik Zouave (Internet Policy Review)
Computer Network Operations (CNOs) refers to government intrusion and/or interference with networked information communication infrastructures for the purposes of law enforcement and security intelligence. The following article explores how CNOs are lawfully authorised in Australia, and considers the extent to which the current use of CNOs are subject to ‘counter-law’ developments. More specifically, the article finds that the scope and application of CNOs in Australia are subject to weak legislative controls, that while such operations might be ‘lawful’, they undermine rule of law and disturb core democratic freedoms.